Noncompliance a Major Threat in Fisheries Management – Experience from the Artisanal Coastal Fisheries of Bangladesh (Journal of International Studies, 2020)
Non-compliance with regulation is a major problem that undermines the effectiveness of the coastal fisheries management in Bangladesh. The result of non-compliance with regulation is over fishing, resource depletion, habitat degradation and resource use conflicts. From a management perspective, it is important to examine the level and causes of non-compliance and explore policies for encouraging or securing compliance. An attempt has been made in this study to investigate these issues in the case of the marine fisheries of Bangladesh. The specific area of interest is the mesh size regulation. Result showed an absolute violation of the mesh size regulation. The study found that the opportunity of getting higher catches and economic returns, weak enforcement, influence of the social environment, ignorance about the law and limited livelihood opportunities are the main causes behind the noncompliance of the fishers with respect to mesh size regulation.